2022
DOI: 10.1101/2022.04.13.488132
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Omicron (B.1.1.529) SARS-CoV-2 variant of concern also affects companion animals

Abstract: The recent emergence of the Omicron variant (B.1.1.529) has brought with it a large increase in the incidence of SARS-CoV-2 disease worldwide. However, there is hardly any data on the incidence of this new variant in companion animals. In this study, we have detected the presence of this new variant in domestic animals such as dogs and cats living with owners with COVID19 in Spain that have been sampled at the most optimal time for the detection of the disease. None of the RT-qPCR positive animals (10.13%) pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…2021; Kim et al., 2020; Shi et al., 2020). Also, considering that both natural and experimental SARS‐CoV‐2 infections in pet animals have mostly caused subclinical infections so far (Hamer, Pauvolid‐Corrêa, et al., 2021; Kim et al., 2020; Ruiz‐Arrondo et al., 2021; Sánchez‐Morales et al., 2022), it is rather difficult to suspect the right timing of active SARS‐CoV‐2 infection. In some cases, SARS‐CoV‐2 infections in pets caused mild clinical signs, mainly respiratory (coughing, sneezing) and digestive (diarrhoea, vomiting) (Fritz et al., 2021; Hamer, Ghai, et al., 2021; Kim et al., 2020), as we observed in the case of D2 (Fernández‐Bastit et al., 2021).…”
Section: Discussionmentioning
confidence: 99%
“…2021; Kim et al., 2020; Shi et al., 2020). Also, considering that both natural and experimental SARS‐CoV‐2 infections in pet animals have mostly caused subclinical infections so far (Hamer, Pauvolid‐Corrêa, et al., 2021; Kim et al., 2020; Ruiz‐Arrondo et al., 2021; Sánchez‐Morales et al., 2022), it is rather difficult to suspect the right timing of active SARS‐CoV‐2 infection. In some cases, SARS‐CoV‐2 infections in pets caused mild clinical signs, mainly respiratory (coughing, sneezing) and digestive (diarrhoea, vomiting) (Fritz et al., 2021; Hamer, Ghai, et al., 2021; Kim et al., 2020), as we observed in the case of D2 (Fernández‐Bastit et al., 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Increasingly, these pets are friends/family members, meaning that owners are in close contact with them daily, which is important when considering virus transmissions between owners and animals. Indeed, anthropozoonotic SARS-CoV-2 transmissions from infected owners to their cats or dogs were reported with increasing frequency and included multiple variants of concern (VOCs) from alpha to omicron [ 5 , 6 , 7 , 8 , 9 ]. Alarmingly, the suspicion of a first cat-to-human back-transmission of SARS-CoV-2 was reported recently [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that SARS-CoV-2 RNA was detected in dogs from households of COVID-19 patients in Hong Kong and Italy [ 21 ]. Moreover, the SARS-CoV-2 Omicron variant (B.1.1.529) has recently been detected in cats and dogs living with COVID-19 patients in Spain [ 22 ]. Another concern is the potential threats of animal CoV variations which may cause the next global pandemic.…”
Section: Introductionmentioning
confidence: 99%